Solving large-scale combinatorial optimization problems - Benson, Steven John (ProQuest Dissertations & Theses, 1998)
I use the positive semidefinite relaxation to approximate combinatorial and quadratic optimization problems subject to linear and boolean constraints. I present a dual potential reduction algorithm and show how it exploits structure and sparsity. Coupled with randomized and heuristic methods, I report computational results for approximating combinatorial problems with dimension up to 7000.